2022
DOI: 10.3390/molecules27206906
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Crystal Structure, In Vitro and In Silico Evaluation of New N′-Benzylidene-4-tert-butylbenzohydrazide Derivatives as Potent Urease Inhibitors

Abstract: Hydrazides play a vital role in making biologically active compounds in various fields of chemistry. These determine antioxidant, antidepressant, antimalarial, anti-inflammatory, antiglycating, and antimicrobial activity. In the present study, twenty-three new N’ benzylidene-4-(tert-butyl)benzohydrazide derivatives (4–26) were synthesized by the condensation of aromatic aldehydes and commercially available 4-(tert-butyl)benzoic acid. All the target compounds were successfully synthesized from good to excellent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…ADMET screening studies have been recognized as fundamental concepts and key tools that were integrated early in the drug discovery phase. These studies served to assist modern project teams in predicting human pharmacokinetics and evaluating the potential of drugs ( Lin et al, 2003 , Ahmad et al, 2022a , Ahmad et al, 2022b ). Different parameters were chosen for ADMET calculations to determine the flux of the best inhibitors within the human body during administration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ADMET screening studies have been recognized as fundamental concepts and key tools that were integrated early in the drug discovery phase. These studies served to assist modern project teams in predicting human pharmacokinetics and evaluating the potential of drugs ( Lin et al, 2003 , Ahmad et al, 2022a , Ahmad et al, 2022b ). Different parameters were chosen for ADMET calculations to determine the flux of the best inhibitors within the human body during administration.…”
Section: Resultsmentioning
confidence: 99%
“…Schiff bases play a crucial role as ligands and are among the most widely used organic substances ( Boulechfar et al, 2023 , Khan et al, 2023 , Luo et al, 2023 ). They can be considered a subclass of imines ( Ahmad et al, 2022a , Ahmad et al, 2022b , Shilpa Laxman, 2022 ), which contain the imine (-C = N-) group in their structure that occurs through the reaction of an aldehyde or ketone with a primary amine under suitable conditions ( Ahmad et al, 2022a , Ahmad et al, 2022b , Nuriye Tuna, 2022 ). The imine group can be part of the 1,2,4-triazole ring ( Jumaa et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The current study is based on the synthesis of novel thiosemicarbazide derivatives of 2,4-dichlorophenylacetic acid in high yields via multistep reactions. In the first step, the starting material 2,4-dichlorophenylacetic acid 1 was refluxed with sulfuric acid (H 2 SO 4 ) in absolute ethanol to get the desired ester 2 ( Ahmad et al, 2022a ). The obtained ester was further refluxed with thiosemicarbazide in the presence of catalytic amount of acetic acid in pure ethanol to get compound 3.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, drugs to treat AD are based on their ability to inhibit cholinesterase enzymes, that is, acetylcholinesterase (AChE) and butyrylcholinesterase (BChE). , Nowadays, various drugs are used for the treatment of AD, including rivastigmine, donepezil, galantamine, and tacrine (Figure ). Synthetic organic chemists are working on new, chief, effective, and safe drugs for AD. , In the near past, our research group has reported imine-containing derivatives with promising biological activities. The present work is mainly focused on the synthesis of various thiosemicarbazone derivatives with anticholinesterase inhibitory potential.…”
Section: Introductionmentioning
confidence: 99%